Effect of the addition of the antioxidant taurine on the complete blood count of whole blood stored at room temperature and at 4ºC for up to 7 days - Sirdah,Mahmoud Mohammed (2013)
BACKGROUND: The complete blood count is one of the most common routine tests. This study aimed to evaluate possible effects of the antioxidant taurine on the complete blood count of whole blood stored at room temperature and at 4ºC over seven days. METHODS: Venous blood samples of 25 healthy males were distributed into two sets of tubes with each set of four tubes containing 50 µL of solutions with zero, 2.5 g/L, 5 g/L, 10 g/L taurine. The tubes were kept at room temperature or at 4ºC. Complete blood counts were performed on seven successive days. The mean percentage changes [Δ = (mean value - mean baseline value) / mean baseline value x 100] were calculated and compared. RESULTS: Complete blood count parameters exhibited different patterns of behavior which were affected by the storage temperature, time and taurine concentration. Taurine at room temperature significantly enhancedthe stability of: the platelet count over seven days (Δ7 at 2.5, 5 and 10 g/L taurine were 5.45, 6.11, and 5.80 x 10(9) cells/L, respectively); the red blood cell count over five days (Δ5 at 2.5, 5 and 10 g/L taurine were 1.59, 2.79, and 1.98 x 10(12) cells/L, respectively); mean corpuscular hemoglobin over five days (Δ5 at 2.5, 5 and 10 g/L taurine were -0.91,-1.52 and -0.84 fl respectively); and red cell distribution width over two days (Δ2 at 2.5, 5 and 10 g/L taurine were 0.90%, 1.30% and -0.1%, respectively). No additional stabilizing effects of taurine were reported for the mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, hematocrit and hemoglobin, while it negatively affected the white blood cell stability. CONCLUSION: Complete blood count parameters exhibited variable stability patterns in respect to temperature, time and taurine concentration.